2008
DOI: 10.1007/s10508-008-9311-7
|View full text |Cite
|
Sign up to set email alerts
|

Visiting Entertainment Venues and Sexual Health in China

Abstract: Entertainment venues in China are associated with risky sexual behavior. Most previous studies related to entertainment venues in China have focused on sex workers and commercial sex, but this study addressed sexual health in a sample of the general urban population. A randomly selected sample of market vendors (n = 4,510) from an eastern city was recruited and assessed to examine relationships between entertainment venue visits and sexual risk. Both behavioral (self-reports of unprotected sex) and biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Given the expanding literature that links sex venues and sexual risk in China, 725 this observation is unexpected. We would offer three potential explanations for this lack of an association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the expanding literature that links sex venues and sexual risk in China, 725 this observation is unexpected. We would offer three potential explanations for this lack of an association.…”
Section: Discussionmentioning
confidence: 99%
“…56 Rapidly expanding entertainment centres and related sex venues have created specific local environments that may increase the likelihood of unsafe commercial sex. 78 A rich anthropological and sociological literature describes densely clustered sex venues that serve as a locus for purchasing and selling sex. 9 Yet sex venues frequented by high-risk groups have also been the site of pilot syphilis testing and control strategies in many parts of China, 10 including Shenzhen.…”
Section: Introductionmentioning
confidence: 99%
“…Missing values accounted for less than 10% of all the respective independent variables. Occupation was dichotomised into entertainment and non-entertainment based on earlier work supporting higher sexual risk behaviours at entertainment establishments 25. First-borns were categorised as being either the eldest or only children.…”
Section: Methodsmentioning
confidence: 99%
“…Occupation was dichotomised into entertainment and non-entertainment based on earlier work supporting higher sexual risk behaviours at entertainment establishments. 25 First-borns were categorised as being either the eldest or only children. Middle-borns had at least one elder sibling and one younger sibling.…”
Section: Methodsmentioning
confidence: 99%
“…We found that male participants who reported visiting entertainment venues were more than five times more likely to report unprotected sex than those who did not. Entertainment venue visits were also significantly correlated with STD infection (Li et al, 2008). HIV prevention in entertainment venues in China needs to go beyond targeting female entertainment workers.…”
Section: Introductionmentioning
confidence: 99%